1986
DOI: 10.1177/002204268601600106
|View full text |Cite
|
Sign up to set email alerts
|

Addiction Careers: Etiology, Treatment, and 12-Year Follow-up Outcomes

Abstract: Follow-up interviews were conducted with 405 black and white male opioid addicts 12 years after admission to drug abuse treatments in the Drug Abuse Reporting Program. Outcomes over time in this longitudinal data system showed that the behavioral improvements observed throughout the first 6-year posttreatment follow-up period (compared with pretreatment baselines) tended to stabilize between Years 6 and 12. About one-fourth of the sample still used opioid drugs daily in Year 12. Demographic and background meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
5

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(38 citation statements)
references
References 13 publications
2
31
0
5
Order By: Relevance
“…Addiction is widely understood as a chronic relapsing disorder, thereby making the prevention of relapse one of the critical elements of effective treatment. Studies have shown that 54% of all alcohol and drug abuse patients can be expected to relapse, and that 61% of those will have multiple episodes of relapse (Simpson, Joe, Lehman & Sells, 1986). The evaluations reported on in this study identified some possible strategies for tackling this challenge.…”
Section: Lessons For Public Treatment Programmesmentioning
confidence: 94%
“…Addiction is widely understood as a chronic relapsing disorder, thereby making the prevention of relapse one of the critical elements of effective treatment. Studies have shown that 54% of all alcohol and drug abuse patients can be expected to relapse, and that 61% of those will have multiple episodes of relapse (Simpson, Joe, Lehman & Sells, 1986). The evaluations reported on in this study identified some possible strategies for tackling this challenge.…”
Section: Lessons For Public Treatment Programmesmentioning
confidence: 94%
“…Hence, the goal of treatment should be the management of addiction, not its cure. Many studies show that the length of stay in treatment is positively related to outcomes (De Leon, 1991;Simpson, 1979Simpson, , 1998aSimpson, Joe, Lehman, & Sells, 1986). However, clients frequently leave drug treatment prematurely; therefore, different strategies must be used to engage and retain addicts in services long enough for them to gain therapeutic benefit from their participation.…”
Section: Availability and Length Of Participationmentioning
confidence: 99%
“…Un certain nombre d'études visant à mesurer l'efficacité des programmes de traitement auprès d'une clientèle judiciarisée ont démontré un pronostic plutôt sombre quant à l'impact du traitement sur ces personnes (Steer, 1980;Simpson et al, 1986;Anglin et Hser, 1990;Beaudet et al, 1995). Ce mauvais pronostic serait attribuable à la faible motivation de cette clientèle à poursuivre une démarche volontaire de réadaptation suffisamment longtemps pour en retirer de véritables béné-fices (Beaudet et al, 1995).…”
Section: Problématiqueunclassified